PENILAIAN KINERJA KOPERASI WANITA SERBA USAHA “SETIA BUDI WANITA” JAWA TIMUR BERDASARKAN PERATURAN MENTERI NO.14/PER/M.KUKM/XII/2009 (PERIODE PENELITIAN 2010-2012) - Faqih Fansuri; Achmad Helmy Djawahir (Jurnal Ilmiah Mahasiswa FEB, 2013)
Performance is an illustration of the level achievement of an activity/program/​policy implementation in achieving goals, objectives, mission and vision of the organization as stated in the strategic planning.  Financial performance assessment was conducted to determine how far the performance of  cooperative can support its achievement. It is expected to give consideration and information material to help management make a decision that can improve its goal achievement. The purpose of this study was to determine the performance and the health level of Women Multipurpose Cooperative Enterprises "Setia Budi Wanita" East Java within 3 years of the study. This assessment is based on Regulation of The Minister No.14/PER/M.KUKM/XII/2009. This study uses a descriptive method. The object is at the Women Multipurpose Cooperative Enterprises "Setia Budi Wanita" East Java using financial data from the Cooperative Financial Statements in the report of Accountability Board and Supervisory Monitoring Results Women Multipurpose Cooperative Enterprises "Setia Budi Wanita" East Java 2010/2011 and 2011/2012. The Financial Statements are  analyzed using financial ratios in every aspect that has been described in the Regulation of the Minister No.14/PER/M.KUKM/XII/2009. The result shows that the health level of Women Multipurpose Cooperative Enterprises "Setia Budi Wanita" East Java is "Healthy Enough”. In the first 2 years (2010 and 2011), the performance level was able to get the title "Healthy Enough". Whereas in 2012, the cooperative was able to get title "Healthy". Keywords: Cooperative Performance, Financial Statement Analysis.